Investigation into nanostructured carbon-based materials for electrochemical applications - Nolan, Hugo (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
Carbon materials, despite their ubiquitousness in nature and long studied properties, continue to be at the forefront of material research today. The last 20-30 years have seen renewed interest in structural allotropes such as fullerenes, nanotubes and graphene; which all bear the same basic bonding structure as graphite. Their discovery has seen an enormous surge in publications of so-called nanocarbons, with an extensive range of applications proposed on the basis of their excellent physical, chemical, electronic, mechanical and optical properties. Although these more recently discovered exotic materials account for the bulk of pubhcations dealing with graphitic carbons, less glamorous but much more processesable materials such as Pyrolytic Carbon (PyC) continue to show great promise in a range of applications.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin